(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
In the current research, the dynamic analysis of bridge structure is conducted to determine the natural frequency and mode shape. The dynamic analysis is conducted using ANSYS FEA simulation package. The critical regions of high deformation and energy states are determined. The analysis revealed the presence of several dominant vibration modes, each associated with distinct deformation patterns and nodal patterns. These findings shed light on potential vulnerability zones and areas of concern that may be susceptible to resonance and excessive vibrations during bridge operation. Understanding these critical modes is vital for designing appropriate damping and vibration control measures to ensure the bridge’s long term stability and safety.